'I did not get this disease on the street; it was brought home as a gift': Gender, violence and HIV vulnerability among Cuban women. Issue 8 (1st August 2022) - Beltrán, Lisandra Fuentes; Davis, Dirk A.; Barrington, Clare; Castro, Marta; Pérez, Dennis
Abstract: While gay, bisexual and other men who have sex with men are most affected by HIV in Cuba, infections among women have increased over time, but there has been little research to contextualise their vulnerability to HIV. The purpose of this study was to explore the role of gender and violence in shaping vulnerability to HIV among Cuban women. Qualitative in-depth interviews were conducted with women living with HIV at an outpatient HIV clinic in Havana. Narrative and thematic technique were used to systematically analyse the data. Participants described negotiating sexual relationships in a context where traditional gender norms merge with the paradox of increasing professional opportunities for women alongside growing economic precarity. Interconnected economic and emotional dependence along with violence influenced the acceptance of certain behaviours that heightened vulnerability to HIV, including inconsistent condom use and infidelity. Gender transformative approaches that recognise the complex interplay between gender norms, economic precarity and violence are needed to address women's vulnerability to HIV in the Cuban context. Such efforts can reinforce existing strategies to promote behaviourally focused prevention while creating an enabling environment for the integration and expansion of biomedical innovation in HIV prevention.